USAHATANI IKAN MAS SISTEM KERAMBA: ANALISIS PENDAPATAN, FAKTOR PRODUKSI, DAN SKALA USAHA - Ida Bagus Made Agung Dwijatenaya (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2017)
This research aims to analyze the benefit, the effects of production factors to revenue the carp farming, and to analyze return to scale. Technique the sample collection with the full simple methods, with the sample of the 33 farmers.  The benefit analyze and the Cobb-Douglas production function assited in answering the goal. The research results show production factos simultaneously effect positive and significant to revenue.  Seeds cost and labors cost effect positively and significant to revenue the carp farming of keramba system. but feeds cost and depreciation cost effect not significantly to revenue.  Return to scale of the carp farming of keramba system  is at the condition increasing return to scale, it means worthy of to be developed.